Constater la mort sans le médecin ? - Anne Carol (Histoire, Médecine et Santé, 2021)
In 1877, the will of a philanthropist, the Marquis d’Ourches, instructed the Academy of Medicine to award two prizes, one of which, endowed with 20 000 francs, for “the discovery of a simple and vulgar means of recognizing, in a certain and indubitable manner, the signs of real death”. Between 1868 and 1874, more than a hundred memoirs reached the Academy from various social backgrounds and countries. This paper studies their authors and their content. It allows us to place the Ourches Prize in the long history of the fear of premature burial and its investment by medicine since the 18th century. This study bears witness to the spread of medical culture among the public, but also to the evolution of the construction of medical knowledge, from observation to experimentation. In the end, by not awarding the prize, the Academy forcefully reaffirms the monopoly of medical expertise in the clinical and legal definition of death.